FROM GLORY TO RUIN THE DYNAMICS OF THE DISINTEGRATION OF THE ABBASID CALIPHATE IN BAGHDAD (750–1258 AD) - Pujiati, pujiati; Syamruddin, Syamruddin (Jurnal Ilmu Pendidikan Islam, 2025)
This research is a literature study that aims to comprehensively examine the process of disintegration of the Abbasid Caliphate in Baghdad from its heyday to its collapse in 1258 AD. As one of the most outstanding dynasties in Islamic history, the Abbasid Caliphate experienced a long period of progress in the fields of politics, economics, science, and culture. However, this glory gradually weakened due to various internal and external factors. Through an analysis of primary and secondary sources, this study finds that the disintegration of the Abbasid Empire was triggered by the weakening of the caliph's authority, the increasing influence of non-Arab military forces, internal political conflicts, and the fragmentation of the territory. External factors such as the Mongol invasion and the weakening of Islamic solidarity also accelerated the destruction of the center of government in Baghdad. This study confirms that the collapse of the Abbasid Caliphate was not the result of a single event, but rather the culmination of multiple multidimensional crises that occurred over a prolonged period. These findings are expected to enrich our understanding of the dynamics of political and social change in the history of classical Islamic civilization.